2023
DOI: 10.3390/ijms241310587
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Screening of Long Noncoding RNAs and Their Target Protein-Coding Genes Unmasks a Dynamic Portrait of Seed Coat Coloration Associated with Anthocyanins in Tibetan Hulless Barley

Abstract: Many plants have the capability to accumulate anthocyanins for coloration, and anthocyanins are advantageous to human health. In the case of hulless barley (Hordeum vulgare L. var. nudum), investigation into the mechanism of anthocyanin formation is limited to the level of protein-coding genes (PCGs). Here, we conducted a comprehensive bioinformatics analysis to identify a total of 9414 long noncoding RNAs (lncRNAs) in the seed coats of purple and white hulless barley along a developmental gradient. Transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 91 publications
1
7
0
Order By: Relevance
“…To comprehensively pinpoint lncRNAs involved in the processes induced by OsOSCA1.1, salt, and hyperosmolarity stress in rice, we conducted lncRNA identification based on 24 RNA-seq data sets [ 32 ]. It contained the seedling roots of ZH11 and ososca1.1 exposed to the solution (hyperosmolarity stress, salt stress, and control) and their corresponding shoots [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To comprehensively pinpoint lncRNAs involved in the processes induced by OsOSCA1.1, salt, and hyperosmolarity stress in rice, we conducted lncRNA identification based on 24 RNA-seq data sets [ 32 ]. It contained the seedling roots of ZH11 and ososca1.1 exposed to the solution (hyperosmolarity stress, salt stress, and control) and their corresponding shoots [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…To make the transcript fit the lncRNA characteristics, we employed an established pipeline to identify lncRNAs in the rice shoots and roots ( Figure 1 a) [ 32 ]. The transcript models were mainly compared with PCG transcripts and classified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, PPO has been suggested to be responsible for melanin production in rice (Fukuda et al ., 2012 ), sesame (Wei et al ., 2016 ), bitter gourd (Zhong et al ., 2022 ), persimmon (Qi et al ., 2020 ) and watermelon (Li et al ., 2019 ). The significance of lncRNA in diverse biological processes is crucial in plant kingdoms, which can modulate the expression of target genes through cis ‐ and trans ‐acting mechanisms; impact the structure and function of chromatin; and participate in RNA transcription, splicing and stabilization (Zheng et al ., 2023 ). Several studies have illustrated the significance of lncRNAs in plant development and colour formation process (Li et al ., 2023 ; Zheng et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of lncRNA in diverse biological processes is crucial in plant kingdoms, which can modulate the expression of target genes through cis ‐ and trans ‐acting mechanisms; impact the structure and function of chromatin; and participate in RNA transcription, splicing and stabilization (Zheng et al ., 2023 ). Several studies have illustrated the significance of lncRNAs in plant development and colour formation process (Li et al ., 2023 ; Zheng et al ., 2023 ). In this study, two Blp_lncRNAs were identified to be significantly co‐expressed with HvBlp , which may be involved in the stage‐ and tissue‐specific expression of HvBlp .…”
Section: Discussionmentioning
confidence: 99%